Respon Petani Terhadap Peran Penyuluh Pertanian dalam Meningkatkan Dinamika Kelompok Tani - Salahuddin Salahuddin; Sukmawati Abdullah; Gede Swanakara (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
Extension workers have a very important role in agricultural development, thus requiring extension workers who have adequate competence. This study aims to analyze the responses of farmers to the role of extension workers in improving the dynamics of farmer groups. The research was conducted in Kasimpa Jaya Village, South Tiworo District. The determination of the research location was carried out using the purposive sampling method. Analysis of the relationship between farmers' responses to the role of extension workers in improving the dynamics of farmer groups using the Spearman Rank Correlation Method. The results showed that the response of farmers to the role of extension agents was low, the dynamics of farmer groups in Kasimpa Jaya Village were good, and the relationship between farmers' responses to the role of extension workers in improving farmer group dynamics was low.